Risky and antisocial behavior in adolescence - Manasse, Michelle E. (The Oxford handbook of developmental psychology and the law, 2024)
This chapter provides an interdisciplinary review of research concerning risky and antisocial behavior during the adolescent years. In particular, it summarizes and integrates existing research concerning two fundamental issues. First, it describes the developmental factors that contribute to the general tendency for risky and antisocial behavior to increase during adolescence. Second, it describes potential sources of interpersonal variation in risky and antisocial behavior during this stage of the life course. For both issues, the chapter discusses research bearing on the ways in which biological factors, family dynamics, the peer group, and the broader community collectively influence risky and antisocial behavior, paying special attention to the ways in which these factors interact to amplify or suppress one another’s influences.